Rancang bangun mesin pengupas tempurung kelapa - Budi Setiawan; Erwin Erwin; Ari Rianto (Universitas Muhammadiyah Metro, 2021)
The first work that must be done on coconuts after the coir stripping process is to strip the coconut shells. This is because the part of the coconut that is processed further is part of the coconut meat itself. Coconut shell is the hardest part of the coconut fruit. On this coconut shell, coconut meat is attached. Manually removing coconut meat will take a relatively long time, around 3-5 minutes for 1 coconut. Of course, with this time the capacity and production efficiency cannot be maximized. This research was conducted with the aim of designing and testing the capabilities of coconut shell peeling machines. This machine is operated by using 2 blades, namely a flat peeler blade as a barrier to the surface of the coconut shell and a toothed peeler to press the surface of the shell. The results of the functional testing of this machine obtained the best value at the rotational speed of the peeler teeth of 14 rpm with an average shelling time of 20.96 seconds per piece.Keywords: coconut, machine, coconut shells, shelling time.